Values for self-build urbanism. Issue 6 (3rd June 2019) - Caputo, Silvio; de Oliveira, Fabiano Lemes; Blott, Dan
ABSTRACT: Self-build is lately attracting much interest as a solution to housing supply that can complement the insufficient delivery of housebuilding by the construction industry. The historical trajectory of self-build shows that from a practice which had a conflictual stance towards central authority in the past, it is now promoted by the same authority within a framework of empowerment of and central power devolution to local communities. Against this backdrop, the challenge is to preserve the spirit of independence that still pervades self-build and yet merge it with the planning frameworks which are used to control development generally. This approach has recently been experimented with by some large-scale self-build projects. Through literature review, this article firstly identifies important values that motivate self-builders; secondly it recognizes rule-based, rather than prescriptive codes such as generative codes, as those that can facilitate autonomy within a loose form of control; and finally it develops case studies that help understand how such values have been interpreted in different ways, reflecting the context. Elaborating on case studies, the discussion section outlines how values can inform different types of generative codes while increasing participation and an enhanced democracy of the planning process.